Longitudinal assessment of ventricular volume trajectories in early-stage schizophrenia: evidence of both enlargement and shrinkage - Svancer, Patrik; Capek, Vaclav; Skoch, Antonin; Kopecek, Miloslav; Vochoskova, Kristyna; Fialova, Marketa; Furstova, Petra; Jakob, Lea; Bakstein, Eduard; Kolenic, Marian; Hlinka, Jaroslav; Knytl, Pavel; et al. (BMC psychiatry, 2024)
BACKGROUND: Lateral ventricular enlargement represents a canonical morphometric finding in chronic patients with schizophrenia; however, longitudinal studies elucidating complex dynamic trajectories of ventricular volume change during critical early disease stages are sparse. METHODS: We measured lateral ventricular volumes in 113 first-episode schizophrenia patients (FES) at baseline visit (11.7 months after illness onset, SD = 12.3) and 128 age- and sex-matched healthy controls (HC) using 3T MRI. MRI was then repeated in both FES and HC one year later. RESULTS: Compared to controls, ventricular enlargement was identified in 18.6% of patients with FES (14.1% annual ventricular volume (VV) increase; 95%CI: 5.4; 33.1). The ventricular expansion correlated with the severity of PANSS-negative symptoms at one-year follow-up (p = 0.0078). Nevertheless, 16.8% of FES showed an opposite pattern of statistically significant ventricular shrinkage during ≈ one-year follow-up (-9.5% annual VV decrease; 95%CI: -23.7; -2.4). There were no differences in sex, illness duration, age of onset, duration of untreated psychosis, body mass index, the incidence of Schneiderian symptoms, or cumulative antipsychotic dose among the patient groups exhibiting ventricular enlargement, shrinkage, or no change in VV. CONCLUSION: Both enlargement and ventricular shrinkage are equally present in the early stages of schizophrenia. The newly discovered early reduction of VV in a subgroup of patients emphasizes the need for further research to understand its mechanisms.
Keywords: dospělí; Magnetic Resonance Imaging; Female; Adult; mladý dospělý; ženské pohlaví; mozkové komory; longitudinální studie; Adolescent; lidé; Lateral Ventricles; magnetická rezonanční tomografie; studie případů a kontrol; Longitudinal design; schizofrenie; Ventricular volumes; First-episode schizophrenia; Male; progrese nemoci; Case-Control Studies; Negative symptoms; Disease Progression; Young Adult; Schizophrenia; Cerebral Ventricles; MRI; mužské pohlaví; ventriculi laterales; mladiství; Longitudinal Studies; Humans